Porcine sperm vitrification I: cryoloops method - Arraztoa, Claudia Cecilia (2016)
The aims of this study were to evaluate porcine sperm vitrification in cryoloops, with and without two different cryoprotectants and assess two warming procedures. Extended (n = 3; r = 4) and raw (n = 5; r = 2) semen was diluted in media without and with cryoprotectants (4% dimethylformamide and 4% glycerol) to a final concentration of 20 × 106 spermatozoa ml−1 and vitrified using the cryoloops method. Two warming procedures were evaluated: rapid method (30 s at 37°C) and an ultra-rapid method (7 s at 75°C, followed by 30 s at 37°C). Total motility (phase contrast), sperm viability (6-carboxifluorescein diacetate and propidium iodide stain), membrane function (hypo-osmotic swelling test), acrosome integrity (phase contrast), chromatin condensation (toluidine blue stain) and chromatin susceptibility to acid denaturation (acridine orange stain) were evaluated before and after vitrification and analysed using Friedman's test. In all media, the only seminal parameters that were maintained after vitrification were chromatin condensation and integrity. Vitrification of porcine spermatozoon using cryoloops, both in the presence or absence of cryoprotectants and independent of the warming procedure used, permits conservation of sperm chromatin condensation and integrity. It would be interesting to further verify this by producing porcine embryos using vitrified spermatozoon with intracytoplasmic sperm injection.